2006
DOI: 10.1007/s11199-006-9336-5
|View full text |Cite
|
Sign up to set email alerts
|

Go Figure? Body-Shape Motives are Associated with Decreased Physical Activity Participation Among Midlife Women

Abstract: This study was designed to investigate the relationship between midlife women's physical activity motives and their participation in physical activity. Cross-sectional qualitative and quantitative data were collected from 59 midlife women, most of whom were well-educated European-Americans (mean age = 45.6 years). Body-shape physical activity motives (i.e., motives related to toning, shaping, and weight loss) were compared with all other types of physical activity motives combined. Participants with body-shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 64 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…The aims of this study were to expand previous research on midlife women's reasons for being physically active (Segar et al 2006) by investigating (a) the specific content of midlife women's most important goals for being physically active; and (b) to validate the clusters using variables that highlight relevant sociocultural beauty/thinness norms and pressures that influence women's physical activity goal selection and those that indicate intrinsic and introjected behavioral regulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aims of this study were to expand previous research on midlife women's reasons for being physically active (Segar et al 2006) by investigating (a) the specific content of midlife women's most important goals for being physically active; and (b) to validate the clusters using variables that highlight relevant sociocultural beauty/thinness norms and pressures that influence women's physical activity goal selection and those that indicate intrinsic and introjected behavioral regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that health-and weight-related physical activity goals are more related to social norms and associated with less optimal behavioral regulation compared to goals related to sense of well-being and stress reduction. These findings are important to consider because there is a body of research suggesting that autonomous regulations, intrinsic motivation and persistence in physical activity behavior may be undermined when women initiate physical activity out of compliance to sociocultural norms and pressures Eccles 2005;Segar et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that midlife women who have body-shape motives are significantly less active than those with nonbody shape motives. 19 Based on these findings, there is a need to examine nonphysical approaches to improving self-worth and PA in women.…”
mentioning
confidence: 99%